Zero Waste Attitude Scale Development Study - Fuat Ozcan; Ali Meydan (Journal of Education in Science, Environment and Health)
The goal of this study is to create the Zero Waste Attitude Scale, which will be used to determine the zero-waste attitude of social studies teacher candidates and to conduct validity and reliability studies. The data for the study were collected with a 5-point Likert-type form from pre-service teachers studying in the social studies teaching department of some universities in Türkiye. Explanatory factor analysis, confirmatory factor analysis (CFA), and reliability studies were performed on the collected data. Cronbach's alpha and McDonald's Omega methods were used for reliability analysis. As a result of the analysis, it was determined that the scale consisted of 27 items and 3 factors. In total, the factors explained 50.09% of the common variance. As a result of the analysis, the fit index values of the scale χ2/sd =1.96, RMSEA=0.06, PGFI=0.70, GFI=0.85, RMR=0.08, SRMR=0.06, NFI=0.95, AGFI=0.81, PNFI=0.84, CFI=0.97, RFI=0.94, NNFI=0.97, IFI=0.97, while GFI, RMR, AGFI, SRMR, and RFI values correspond to acceptable fit; χ2/sd, RMSEA, IFI, NFI, NNFI , PGFI, PNFI, and CFI seem to correspond to a perfect fit. The reliability coefficient of the scale was 0.90 for both Cronbach Alpha and McDonald's Omega. The scores obtained from the scale are valid and reliable.